Re-examining the Impact of Globalisation On Economic Growth: Evidence from South America - Muhammad Ariff Azhan Norlia; Chia, Yee Ee (Penerbit UMS, 2021)
This study aims to re-examine the relationship between globalization and economic growth in nine South America countries using the new KOF globalization index. The new improvement version of globalization index contains 43 variables compare to only 23 variables in the Dreher (2006) version which is more precisely quantifies the all-encompassing concept of globalization. The new index of globalization includes both de facto and de jure measures that would influence economic growth differently in certain countries. The data spanning a 17-year period from 2002-2018. Our baseline pooled Ordinary Least Squares (OLS) regression model finds that globalization is positively and significantly associated with higher economic growth. This suggests that globalization improves growth in overall South America countries. Hence, our key findings are supported with a battery of robustness tests, namely Fama-MacBeth, quantile regression, and firm fixed effects.